2016
DOI: 10.4049/jimmunol.1501831
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of Th17 Cells in Autoimmune Kidney Diseases

Abstract: The ability of CD4+ T cells to differentiate into pathogenic Th1 and Th17 or protective T regulatory cells plays a pivotal role in the pathogenesis of autoimmune diseases. Recent data suggest that CD4+ T cell subsets display a considerable plasticity. This plasticity seems to be a critical factor for their pathogenicity, but also for the potential transition of pathogenic effector T cells toward a more tolerogenic phenotype. The aim of the current study was to analyze the plasticity of Th17 cells in a mouse mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 37 publications
0
25
0
1
Order By: Relevance
“…Given the wealth of evidence for Yap in stem cell regulation and the coordination of Yap inactivation with cell differentiation, we hypothesized that deletion of Yap alters the ability of CD4 + T cells to differentiate. To test this hypothesis, we isolated naïve CD4 + T cells from WT and Yap-cKO mice and cultured them under Th1, Th17 and Th2 polarizing conditions (Geng et al, 2017;Krebs et al, 2016). We found that Yap deleted CD4 + T cells showed significantly enhanced Th1, Th17, and Th2 differentiation compared to WT cells, demonstrated by increased intracellular IFNg, IL-17, and GATA3 expression, respectively (Figure 2A-C).…”
Section: Yap Inhibits Cd4 + T Cell Differentiationmentioning
confidence: 97%
“…Given the wealth of evidence for Yap in stem cell regulation and the coordination of Yap inactivation with cell differentiation, we hypothesized that deletion of Yap alters the ability of CD4 + T cells to differentiate. To test this hypothesis, we isolated naïve CD4 + T cells from WT and Yap-cKO mice and cultured them under Th1, Th17 and Th2 polarizing conditions (Geng et al, 2017;Krebs et al, 2016). We found that Yap deleted CD4 + T cells showed significantly enhanced Th1, Th17, and Th2 differentiation compared to WT cells, demonstrated by increased intracellular IFNg, IL-17, and GATA3 expression, respectively (Figure 2A-C).…”
Section: Yap Inhibits Cd4 + T Cell Differentiationmentioning
confidence: 97%
“…83 Pathogenicity of Th17 to Th1 trans-differentiation has been demonstrated also in the context of graft-versus-host disease 84 while, on the contrary, Th17 cells seem phenotypically stable in the autoimmune kidney diseases. 85 The last finding suggests that the microenvironment directs Th17 plasticity. In this view, the microbiome can play a crucial role because bacteria or their products interact with T cells at mucosal surfaces.…”
Section: Th17 To Th1 Cell Plasticity and Diseasementioning
confidence: 97%
“…In addition, non‐classic Th1 cells, as well as classic Th1, produce TNF‐ α , which directly induces CD106 expression by synovial fibroblasts, so promoting leukocyte retention in the inflamed joints . Pathogenicity of Th17 to Th1 trans‐differentiation has been demonstrated also in the context of graft‐versus‐host disease while, on the contrary, Th17 cells seem phenotypically stable in the autoimmune kidney diseases . The last finding suggests that the microenvironment directs Th17 plasticity.…”
Section: Th17 To Th1 Cell Plasticity and Diseasementioning
confidence: 99%
“…In a recent study, we have addressed the plasticity of renal Th17 cells in more detail [44]. After transfer of highly purified in vitro polarized Th17 cells from fluorescence reporter mice [45] and subsequent induction of crescentic glomerulonephritis, reanalysis of T cells from the kidney displayed a relatively high degree of stability.…”
Section: The Fate Of Th17 Cells In Glomerulonephritismentioning
confidence: 99%
“…Moreover, using IL-17A fate reporter mice [19], these findings were confirmed in immunocompetent mice in two models of experimental glomerulonephritis. Importantly, in these studies, no relevant transdifferentiation into Th1 or Th2 cells was detected among ex-Th17 cells [44], leaving their fate unknown. In this context, it is important to note that Th17 cells have been reported to have a high rate of instability and conversion into Th1 cells in nonrenal models of autoimmune diseases [19].…”
Section: The Fate Of Th17 Cells In Glomerulonephritismentioning
confidence: 99%